Exploring heart failure prevalence and dimensions: A comprehensive NT‐proBNP study in high‐risk primary care patients - Ahmet Celik; Emrah Yesil; Unal Kılıç; Gizem Akcay Ozyurt; Selman Aytimur; Mustafa Demir; Huseyin Naci Eker; Ayse Siddika Col; Cemil Ilker Altiparmak; Mustafa Ergen; Selen Bozkaya; Ismail Sefa Okyay; et al. (ESC Heart Failure)
Abstract Introduction Early detection of heart failure (HF), particularly in asymptomatic individuals, is essential for timely intervention. This study aimed to determine the prevalence of HF among high‐risk individuals in primary care using N‐terminal probrain natriuretic peptide (NT‐proBNP) screening. Methods A prospective cohort of 874 participants aged ≥40 years with at least one HF risk factor but no prior HF diagnosis was analysed. NT‐proBNP levels were measured, and all participants underwent comprehensive cardiac evaluations, including laboratory tests, electrocardiography and echocardiography. Results The mean age of the cohort was 62.5 ± 9.1 years, and 51.9% were female. Based on ACC/AHA HF staging, 69.1% of participants were classified as Stage A, 21.9% as Stage B and 9.0% as Stage C. Elevated NT‐proBNP levels were detected in 84.8% of Stage B and 100% of Stage C patients. Among Stage C patients, 92.4% had HF with preserved ejection fraction (HFpEF). NT‐proBNP levels correlated positively with left atrial volume index (r = 0.273, P < 0.001), left ventricular mass index (r = 0.207, P < 0.001), E/e′ ratio (r = 0.182, P < 0.001) and estimated systolic pulmonary artery pressure (r = 0.124, P < 0.001), while showing a negative correlation with estimated glomerular filtration rate (r = −0.222, P < 0.001). Conclusions A significant proportion of high‐risk individuals in primary care had undiagnosed HF, particularly Stage B (pre‐HF) and early symptomatic Stage C HF. The predominance of HFpEF highlights the need for targeted management. NT‐proBNP screening is a valuable tool for early identification and risk stratification, especially for detecting Stage B HF, where it serves as an effective standalone method in the absence of imaging.